Optimising reflective capacity of nursing students after high fidelity simulation: A practical approach - Naomi Tutticci; Fiona Coyer; Mary Ryan (Bond University, 2021)
Navigating simulation as a nursing student is challenging. It requires critical thinking, high levels of reflection and emotional investment. Reflection fatigue can result from knowing that reflection is important but feeling reluctant to expose oneself to critique. This practical discussion explores how nurse educators can optimise nursing students' reflective thinking within simulation and develop debrief strategies that optimise critical reflection. Debrief is a teaching and learning episode within simulation that aims to challenge students to develop their thinking and practice, without compromising instruction. Much debrief practice tends towards instruction at the expense of student self-exploration, and preparation for assessment at the cost of critical reflection. The practical approach to debrief discussed here is a timely reminder to step back and re-assess the practice of debrief. This discussion will assist nurse educators to implement a debrief that supports reflection at the highest level. Four familiar strategies of teaching and learning, when combined within debrief, can optimise the reflective capacity of nursing students: role modelling and vicarious observation, scaffolding of reflective thinking, emotional processing, and student-centred reflection. The practical strategies presented are relevant to both Australian and international nursing higher education contexts.